EFFECT OF FERTILIZER LEVEL, SEED RATE AND SEED SIZE ON YIELD OF POTATO IN ACIDIC SOILS OF MANIPUR - Singh, K P; Singh, R K; Singh, S N; Singh, V K (Potato Journal, 2013)
A field experiment was carried out for two consecutive seasons (2000-2002) at Imphal to find out the suitable combination of seed rate, seed size and fertility level for getting high yield of potato. Significant increase in tuber yield was recorded with increase in fertilizer application from lower (50 N: 50 P: 25 K, kg/ha) to medium level (100 N: 100 P: 50 K; kg/ha). Further increase in fertility levels i.e. 150 N: 150 P: 100 K; kg/ha gave only 5.3% more tuber yield, which was not significantly different from that obtained with the medium fertility level. The tuber yield increased with increase in seed rate upto 25 q/ha. The production of large and medium size tubers increased significantly up to medium fertility level. Seed size had no significant effect on total tuber yield. Seed rate of 25 q/ha and NPK dose of 100 : 100 : 50 kg/ha were found suitable for getting high yield of potato in Manipur region.